Towards Selecting an Optimal Bonding Test Method for Rebar–Concrete: Comparison Between Pull-Out Test and Full-Beam Test - Sisi Chao; Chenghua Li; Jiahong Dong; Ziliang Lu (Buildings)
There are many methods for evaluating the bond behavior between rebar and concrete. For certain experimental purposes, selecting the ideal method for testing the rebar–concrete bonding properties is often a controversial problem. The most representative single-end pull-out test method and the full-beam test method were applied in this work to conduct bonding tests between rebar and concrete. Considering the influence of the concrete strength, bonding length, stirrup, and rebar slotting, these two testing strategies are compared and analyzed in terms of the specimen failure mode, bonding strength, bond–slip curve, and rebar stress distribution. Suggestions are offered regarding the selection of an appropriate method for evaluating the bond behavior between rebar and concrete based on an comparative analysis of the two tested approaches. The results presented herein provide a basis for the preparation of relevant test method standards.